The impact of GMC collisions on the star formation rate - Hunter, Glen H.; Clark, Paul C.; Glover, Simon; Klessen, Ralf S. (Arxiv, 2021)
We simulate the collision of two Giant Molecular Clouds (GMCs) using the movingmesh magnetohydrodynamical (MHD) code AREPO. We perform a small parameterspace study on how GMC collisions affect the star formation rate (SFR). The pa-rameters we consider are relative velocity, magnetic field inclination and simulationresolution. From the collsional velocity study we find that a faster collision causes starformation to trigger earlier, however, the overall trend in star formation rate integratethrough time is similar for all. This contradicts the claim that the SFR significantlyincreases as a result of a cloud collision. From varying the magnetic field inclinationwe conclude that the onset of star formation occurs sooner if the magnetic field isparallel to the collisional axis. Resolution tests suggests that higher resolution delaysthe onset of star formation due to the small scale turbulence being more resolved.
Gesehen am 21.09.2022